2020
DOI: 10.1126/science.aaz2511
|View full text |Cite
|
Sign up to set email alerts
|

A physics-based method that can predict imminent large solar flares

Abstract: Solar flares are highly energetic events in the Sun’s corona that affect Earth’s space weather. The mechanism that drives the onset of solar flares is unknown, hampering efforts to forecast them, which mostly rely on empirical methods. We present the κ-scheme, a physics-based model to predict large solar flares through a critical condition of magnetohydrodynamic instability, triggered by magnetic reconnection. Analysis of the largest (X-class) flares from 2008 to 2019 (during solar cycle 24) shows that the κ-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 41 publications
7
67
2
Order By: Relevance
“…Longer‐term SEP forecasts would first and foremost depend on understanding and predicting solar activity more generally. Recently, progress has been made in flare forecasting (e.g., Chen & Wang, 2020, Kusano et al., 2020. X. Wang et al., 2020), and it is expected that with machine learning patterns leading up to eruptions (flares and CMEs) can be recognized even more reliably.…”
Section: An L4 Mission That Is Critical For Human Explorationmentioning
confidence: 99%
“…Longer‐term SEP forecasts would first and foremost depend on understanding and predicting solar activity more generally. Recently, progress has been made in flare forecasting (e.g., Chen & Wang, 2020, Kusano et al., 2020. X. Wang et al., 2020), and it is expected that with machine learning patterns leading up to eruptions (flares and CMEs) can be recognized even more reliably.…”
Section: An L4 Mission That Is Critical For Human Explorationmentioning
confidence: 99%
“…It is still a difficult part to realistically model this procedure from the solar interior to solar surface and to use it for prediction of sunspot evolution. Zhang et al (2021) and as shown by e.g., Bamba and Kusano (2018) and Kusano et al (2020). However, this topic is still a challenging key topic during the PRESTO interval.…”
Section: Future Topic For Predictability Of Solar-terrestrial Couplingmentioning
confidence: 98%
“…onset. A considerable work forward has however made in recent years in this topic using empirical predictors (e.g., 125 Kontogiannis et al, 2018), machine learning (Florios et al, 2018) and physics-based approaches (Kusano et al, 2020).…”
Section: Predictability Of Coronal Mass Ejections and Solar Flares 105mentioning
confidence: 99%